Downward Wage Rigidity and Job Mobility - Thomas Cornelißen; Olaf Hübler (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
Using data from the German Socio-Economic Panel (GSOEP) we study whether being individually affected by downward wage rigidity has an effect on layoffs, quits and intra-firm mobility. Within a structural empirical model we estimate the individual extent of wage rigidity. This is expressed by the wage sweep-up, which measures by how much individual wage growth increases through the effect of downward wage rigidity when compared to a counterfactual labour market with flexible wage setting. We find robust negative effects of wage sweep-up on quits and layoffs and some evidence for a positive association of wage sweep-up and promotion opportunities. This is consistent with a core-periphery view of the labour force, where a core work force is protected from layoffs and wage cuts and at the same time enjoys good promotion opportunities. On the other side a peripheral work force provides a buffer for adjustment and suffers from both flexible wages, more insecure jobs and less internal promotion opportunities.
Keywords: J63; J31; 330; wage rigidity; wage sweep-up; quits; layoffs; promotions